Pressure control of an electro-hydraulic actuated clutch via novel hysteresis model. (October 2019) - Jung, Sanghun; Choi, Seibum B.; Ko, Youngho; Kim, Jinsung; Lee, Hoyoung
Abstract: This paper mainly focuses on the development of pressure tracking control logic of electro-hydraulic actuators for vehicle application. This is done to improve and ensure the performance of a precise lower-level controller for evolving modern shift control logic. The required performance is obtained by hysteresis model-based feed-forward control and additional feedback control. The hysteresis and the time delay, which adversely affect pressure control, are well known nonlinear behaviors in electro-hydraulic actuators. In order to cope with the hysteresis, a novel hysteresis model is proposed based on a physical phenomenon. A mathematical model based on a characteristic curve obtained in preliminary experiments is presented using only one tuning parameter, and this model can be inverted easily to construct a feed-forward controller. In addition, a feedback controller is designed considering the stability margin of a time delay system. The feedback control inputs ensure compensation of the feed-forward errors caused by model error and uncertainty. The proposed controller is designed to lower computational cost considering applicability for production vehicles. As a result, the developed pressure controller is applied to a transmission control unit of a production vehicle and verified experimentally for various driving scenarios. Highlights: A novel hysteresis model for an electro-hydraulic actuator is developed based on physical phenomena. A feed-forward controller for clutch pressure control is developed using the proposed hysteresis model. A feedback controller with time delay is designed to compensate model uncertainties and disturbances. The performance of the proposed clutch pressure controller is verified by production vehicle experiments.